Religious organization hospital business sustainability in the covid-19 pandemic - Sundari, B.; Kusrina, B Lina; Natalina, Ary (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this research is to analize Covid-19 outbreak have impact with healthcare sector’s financial performance. Parameter that used are liquidity ratio, profitability ratio and solvability ratio. Result will show from the difference of financial performance before and after pandemic. Two type of data that being used are secondary and analysis data. Secondary data is in the form of financial statement from private hospital owned by religious organization. Analysis data that being used are comparison between financial statement in 2019 and 2020 from related hospital as an illustration of condition before and after Covid-19 pandemic. Research variable that used in this paper are liquidity ratio proxied by current ratio, profitability ratio proxied by profit margin and solvability ratio proxied by debt to-equity ratio. The result indicate there is no significant difference towards liquidity ratio, solvability ratio, and profitability before and after Covid-19 pandemic outbreak. Prediction of financial performance for the next 5 years in terms of liquidity will show some increase as show in solvability’s term. As opposed, in terms of profitability will show some decrease. The research outcome expected to be suggestion for management to conduct efficiency and evaluation related to debt management.